Evaluation of results of physical therapy v/s intra articular steroid injection in periarthritis of shoulder: a comparative prospective study - Jain, Ravi Kant; Nagar, Jagdish; Jayaswal, Abhijeet (International Journal of Research in Orthopaedics, 2019)
Background: Frozen shoulder or adhesive capsulitis is a condition where the patient experience stiffness and pain in joint of the shoulder. It is an enigma as till now its etiology is unknown. It affects both the genders of the middle and elderly age. A retrospective, comparative study was to evaluate the effects of physical therapy versus intra-articular steroid injection in periarthritis of shoulder. Methods: 30 patients each with frozen shoulder who were treated either using physical therapy (Group 1) and intra-articular steroid injection (Group 2). The data was collected at baseline and at different follow-up periods and analyzed. Results: There were 3 lost to follow-up in physiotherapy group and 4 in intra-articular injection group. Slight male preponderance (51.9% vs. 48.1%) was seen in physiotherapy group. Left side more affected in both the groups. Literacy (p=0.064), socioeconomic status (p=0.22), occupation (p=0.866), comorbidities (p=0.974), abnormal x-ray (p=0.34) were all comparable between the two groups. Mean duration of shoulder pain and restriction of shoulder motion were also comparable (p>0.05). Side effects– 46.2% were higher in intra-articular injection group. Response to treatment, disability score and SPADI index showed significant reduction in both the groups, but significantly more reduction in intra-articular injection was seen in comparison to the physiotherapy group. Conclusions: The overall treatment outcome in intra-articular injection group is much better in comparison to the physiotherapy group, but with higher side effects. Intra-articular injection of steroid will prove to be a boon after effective management of side effects.